Analisis Indeks Vegetasi Menggunakan Citra ALOS AVNIR-2 untuk Mengestimasi Serapan Karbon - Harry Tetra Antono (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2013)
Forests has an important role in stabilize CO2 concentrations in the atmosphere as a source ofcarbon emissions and can absorb carbon and store. It is often called a carbon sink program . Todevelop this program, it needs carbon stock data stored in the form of biomass using an effectivetechnique and easy to use. This study aimed to estimate the carbon content in the area ofreclamation and secondary forest resulting from mining activities through biomass allometricequation. Biomass values obtained by non-destructive method of sampling and biomass values wereused to develop allometric equations using regression analysis between the biomass with a diameterof tree. The study case was located at mine concession of PT. Lanna Harrita, at the border of KutaiKertanegara and West Kutai Districts, East Kalimantan Province. The allometric biomass equationsfor the reclamation area: B = 0.1 x 0.41 x D2+0.62, and for secondary forests: B = 0.118 x D2,31.Allometric equations to estimate carbon stored is y = 278.91 (NDVI) from 2 to 133.66 (NDVI) +68.4.This study also analysed the carbon stored using remote sensing. The analytical result from theAlos Palsar images of study area PT Lanna Harrita describes that carbon sink potential is 12,229ton/ha in reclamation area and 56,665 ton/ha in secondary forest. The estimation of carbon uptakein low vegeation area of PT Lanna Harrita is 337.037,72 ton/ha, 899.678,1 ton/ha in vegetation isbeing and 43.364,95 in high vegetation.Those data suggest that the reclamation activity in the studyarea gave a little contribution to the carbon sink program yet.